Anxiety Manifestations Typical of Senior Preschool Children - Busegenovna Konysbaeva, Alia; Shapaevna Karakulova, Zaure; Kozybaevna Kyyakbaeva, Ulbosyn; Saparbaikyzy, Sholpan; Ayapbergenova, Almira (Opción, 2019)
The article presents the results of an experimental study of anxiety manifes- tations common to preschool children. The respondents are preschool chil- dren aged between five and six years who attend kindergartens. The authors of the article have analyzed the relationship of anxiety and personality de- velopment (personality traits), including forming self-esteem and emotional intelligence, as well as the sociometric status and the manifestation of fears in senior preschoolers. They have also provided graphic information on the established correspondence between the obtained measurement parameters. The article interprets the established dependencies according to the obser- vation results and answers provided by parents and caregivers during the survey. It also concludes about anxiety manifestations in senior preschool- ers with due regard to primary mental structures of this age. The article highlights the significance of the results obtained in providing psychological and pedagogical assistance to the emerging personality of a preschool child.